1999
DOI: 10.1007/pl00006487
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Substitution Rate of Mammalian Mitochondrial Genomes

Abstract: We present here for the first time a comprehensive study based on the analysis of closely related organisms to provide an accurate determination of the nucleotide substitution rate in mammalian mitochondrial genomes. This study examines the evolutionary pattern of the different functional mtDNA regions as accurately as possible on the grounds of available data, revealing some important "genomic laws." The main conclusions can be summarized as follows. (1) High intragenomic variability in the evolutionary dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
309
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 417 publications
(322 citation statements)
references
References 52 publications
11
309
1
1
Order By: Relevance
“…Using this method, substitution rates were 4.8% (4.32-5.36%), 4.6% (3.59-5.5%), and 4.4% (4.0-4.69%) per Myr for gray, humpback, and minke, respectively. Regardless of the method used, all rates are significantly higher than control region substitution rates estimated from divergence dates using the fossil record (e.g., Pesole et al 1999;Rooney et al 2001;Roman and Palumbi 2003), which range from 1.5% to 2% per Myr. Although no error estimates are available for earlier rates, confidence intervals for cytochrome b calibrated rates do not approach these earlier values.…”
Section: Estimating Control Region Rate Using Individuals Identical Amentioning
confidence: 85%
See 2 more Smart Citations
“…Using this method, substitution rates were 4.8% (4.32-5.36%), 4.6% (3.59-5.5%), and 4.4% (4.0-4.69%) per Myr for gray, humpback, and minke, respectively. Regardless of the method used, all rates are significantly higher than control region substitution rates estimated from divergence dates using the fossil record (e.g., Pesole et al 1999;Rooney et al 2001;Roman and Palumbi 2003), which range from 1.5% to 2% per Myr. Although no error estimates are available for earlier rates, confidence intervals for cytochrome b calibrated rates do not approach these earlier values.…”
Section: Estimating Control Region Rate Using Individuals Identical Amentioning
confidence: 85%
“…We first scaled all H values for cytochrome b and the control region by their appropriate (phylogenetically derived) mutation rates in order to account for functional constraints on evolutionary rate (resulting in units of Ne), since any relative constraints due to function should be reflected in substitution rates. The evolutionary rate of different segments of the mitochondrial genome in whales and other mammals has previously been estimated by comparing genetic distance between species at a given marker against divergence dates for those species (Pesole et al 1999;Roman and Palumbi 2003). Phylogenetic analyses indicate that the control region is evolving at a rate of roughly 1.5-2% per million years (Myr) in whales (Pesole et al 1999;Roman and Palumbi 2003), and cytochrome b is evolving at a rate of about 0.4% per Myr (Alter et al 2007).…”
Section: Obtaining Dna Sequence Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, COX1 and other mitochondrial‐encoded cytochrome c oxidase genes are the least variable of all mitochondrial genes (Pesole et al. 1999; da Fonseca et al. 2008), apparently subject to strong purifying selection and functional constraint (Kerr 2011).…”
Section: Speciation Via Mitonuclear Coevolution To Maintain Coadaptationmentioning
confidence: 99%
“…Bohr and Dianov have reported that this mechanism can repair excision and bases caused by oxidative insult (Bohr and Dianov, 1999). The mitochondrion also replicates rapidly, without a significant proofreading system and has a mutation rate 10-100 times higher than that of nuclear DNA (nDNA) (Pesole et al, 1999).…”
Section: Introductionmentioning
confidence: 99%